Education in Confinement: The Reintegration of Young People in Prison in La Araucanía, Chile - Huaiquián‐Billeke, Claudia (Social Inclusion, 2021)
This article addresses the social reintegration of young people studying in the prison of La Araucanía, Chile. Our objective is to describe the social representation of young people between 19 and 29 years old, who are currently serving a custodial sentence, in their reintegration process after secondary education. We start off with the acknowledgement that both social mobility and educational career are historically marked by the reproduction of sociocultural inequality: Educational structures do not fulfill the mission of providing tools for a persons’ life. Our article is based on a unique case study in which a current phenomenon is investigated; in this case, social reintegration within an authentic context—prison. Semi‐structured interviews were applied during our research and participants’ narratives were methodologically triangulated. Our article concludes that, given the presence of homogenizing and inefficient study plans, young people demand deep changes that are linked to a social pedagogy, which values their skills and life project through an awareness process. This process would enable them to explore their reality and cultural action in order to become conscious young people and co‐creators of their future once in freedom.